2018
DOI: 10.1155/2018/3505371
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Pigeon Behavior Outcomes Using Functional Connections among Local Field Potentials

Abstract: Recent studies indicate that the local field potential (LFP) carries information about an animal's behavior, but issues regarding whether there are any relationships between the LFP functional networks and behavior tasks as well as whether it is possible to employ LFP network features to decode the behavioral outcome in a single trial remain unresolved. In this study, we developed a network-based method to decode the behavioral outcomes in pigeons by using the functional connectivity strength values among LFPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The clustering coefficient, a topological characteristic of the functional network reflecting the intensity of the connection between different channels [34], was calculated, which refers to the possibility that the spatially adjacent channels of a certain channel in the network are also adjacent to each other. Taking a social network in life as an example, it can be compared to the possibility that one's friends are also friends with each other.…”
Section: Functional Network Connectivity Analysismentioning
confidence: 99%
“…The clustering coefficient, a topological characteristic of the functional network reflecting the intensity of the connection between different channels [34], was calculated, which refers to the possibility that the spatially adjacent channels of a certain channel in the network are also adjacent to each other. Taking a social network in life as an example, it can be compared to the possibility that one's friends are also friends with each other.…”
Section: Functional Network Connectivity Analysismentioning
confidence: 99%
“…Compared to electrophysiological measurements, these studies of dynamic functional connectivity with fMRI are inherently limited to the coarse time-scale due to the low-pass filtering effect of the hemodynamic response. Furthermore, a few LFP-based studies of functional connectivity recorded only a few (no more than 32) channels of signals from only one or two brain structures, even in rat (Wei et al 2015;Qi et al 2017) and pigeon (Chen et al 2018), whose brain sizes are much bigger than that of mouse. In contrast, our work is based on super-long LFP signals recorded from thirteen distinct brain regions, with outstanding temporal resolution over fMRI-based studies and finer spatial scale compared with other LFP-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have shown that both Hp and NCL cells of birds are significantly correlated to their learning and cognitive functions [ 80 ]. The rhythm and functional network analyses of the Hp [ 81 ] and NCL [ 64 , 82 ] activities in the studies on the encoding mechanism of pigeon’s goal-directed behavior have shown that both of them participate in the related information encoding, confirming their important roles in goal-directed behavior. The researchers believe that Hp of pigeons focuses on the encoding of the current location and goal location, while NCL focuses on the encoding of routing information related to goal-directed behavioral decision-making.…”
Section: The Role Of Hp-ncl Local Network In Goal-directed Route Imentioning
confidence: 90%
“…The results in the plus-maze based goal-directed experiment in pigeons highlighted the decision-making function of NCL [ 62 ]. Further study has indicated that the increased gamma band (40–60 Hz) energy of local field potential (LFP) in NCL is significantly correlated to the goal-directed behavior during the decision-making process [ 63 ], and the functional connectivity of the functional network based on the multi-channel spike and LFP activities in NCL can be used for goal-directed behavioral outcomes decoding effectively [ 64 ], confirming the role of NCL in the navigational behavior of pigeon on different scales. In addition, for the reward encoding in goal-directed behavior, studies have shown that the activities of NCL were modulated by the value of the reward that would be received based on the reward amount and the delay to reward [ 65 , 66 ], which confirms that NCL has the function of reward encoding to achieve a specific purpose.…”
Section: The Role Of Ncl In Goal-directed Route Information Encodimentioning
confidence: 99%